Atrial fibrillation - A rare arrhythmia after electrical burns - Archita Makharia; Vineet Tiwari; Kishan Gopal Barupal; Manoj Lakhotia (Wolters Kluwer Medknow Publications, 2022)
Electrical injuries are a commonly encountered hazard at both home and the workplace. While most electric-induced arrhythmias are conduction abnormalities or ventricular tachycardia, atrial fibrillation is uncommon. Sparse literature and lack of systematic recommendations on this topic create a challenge in treating such patients. We present a case of a young man who developed atrial fibrillation with fast ventricular rate after an episode of electrical burns, which was reverted successfully with beta-blockers.